2019
DOI: 10.1002/chem.201901313
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanowire‐Templated Molecular Nanopatterning and Nanoparticle Assembly for Surface‐Enhanced Raman Scattering

Abstract: Developing simple and cost‐efficient methods for fabricating molecular patterns is of great importance in the field of nanoscience and nanotechnology. Here, a simple and convenient method was developed for fabricating nanopatterns composed of positively charged silane molecules by using silver nanowires as templates. The as‐obtained silane pattern copies the shape of the silver nanowires and is only 0.7 nm thick, which can later be used for templated assembly of small molecules and nanoparticles of opposite ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Since the discovery of the surface plasmon (SP), it has attracted much attention due to the promising applications in the fields of photonics, , sensing, , biomedicine, etc. Recently, it has been demonstrated that many chemical reactions could be catalyzed or promoted with the aid of plasmonic nanostructures .…”
mentioning
confidence: 99%
“…Since the discovery of the surface plasmon (SP), it has attracted much attention due to the promising applications in the fields of photonics, , sensing, , biomedicine, etc. Recently, it has been demonstrated that many chemical reactions could be catalyzed or promoted with the aid of plasmonic nanostructures .…”
mentioning
confidence: 99%
“…Nanocrystals, especially semiconductor ones, usually possess unique chemical, electrical, optical and magnetic properties compared to their bulk counterparts . These properties are highly dependent on the chemical composition, size, shape and surface state of the nanocrystals . Therefore, controlled synthesis of nanocrystals is becoming a hot topic in many fields, and lots of efforts have been made to precisely control the morphology and surface state of the nanocrystals .…”
Section: Figurementioning
confidence: 99%
“…More importantly, the energy level structure of a molecule can be fine-tuned easily by substitution, making it easier to be aligned with the band structure of a plasmonic metal. By using plasmon-enhanced Raman spectroscopy, [16][17][18] our group has reported thiophenol molecule-induced acceleration of plasmon-mediated chemical reactions. [19,20] However, the contribution of the thiophenol molecules is not clear and the modulation of these reactions with molecular grafting needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%